Chemical characteristics and storage stabilities of different cold-pressed seed oils - Dedebas, Tugba; Ekici, Lutfiye; Sagdic, Osman (WILEY, 2021)
The objective of the study was to evaluate the storage stabilities and chemical characteristics of cold-pressed seed oils, stored for a period of 12 months in a refrigerator (4 degrees C), at room temperature (20 degrees C), and at an elevated temperature (37 degrees C). The physicochemical and bioactivity properties of seed oils were investigated during storage. The total phenolic content and antioxidant activity for coriander seed oil (157.26 mg GAE/100 g; IC 50:560.47 mu g/mL) were higher than those of the others seed oils. The results showed that peroxide value, oxidative indices (K232 and K270), and p-anisidine values changed with the rise in temperature. In this study, it was demonstrated that the magnitude of oxidative deterioration in the samples was the highest when stored at 37 degrees C. Additionally, the storage time and temperature severely affected the shelf life of the oils. Practical applications Cold-pressed oils are not subjected to a high level of heat treatment and solvent treatment during their production, less changes are observed in bioactive components compared to refined oils, and consumer preference is concentrated in these oils. They are quite susceptible to oxidation, easily initiated by factors such as light and temperature. During processing and storage of foods, the oxidative stability of oils is of great importance for obtaining products of high quality and health. In the present study, the main aim was to investigate the stability of seed oils obtained from commercial plants during the storage.
Keywords: VOLATILE OXIDATION COMPOUNDS; CORIANDRUM-SATIVUM L.; BLACK CUMIN; QUALITY CHARACTERISTICS; ANTIOXIDANT ACTIVITY; MINOR COMPONENTS; FLAXSEED OILS; GRAPE SEED; SUNFLOWER; COMPOUND; Food Science & Technology